AL-FALAH SEBAGAI PENANGKAL SISTEM EKONOMI KAPITALIS - ibrahim, bukhari; Kahfi, Muhammad; Muchlis, Saiful (JSE: Jurnal Sharia Economica, 2024)
Current economic developments are generally pioneered by the spirit of capitalism. This study discusses the concept of al-falah in counteracting capitalism in the economic system. This study uses a Qualitative-Descriptive approach method with techniques through literature analysis involving a review of various sources. The results of the study indicate that al-falah can make the economy free from the spirit of capitalism that only benefits certain parties. Therefore, the concept of al-falah, and capitalism which is an obstacle to Islamic economics, is still an interesting discussion to study. Capitalism is an economic system based on the principle of individual freedom to carry out economic activities. This system has provided many benefits to society, but also has a number of weaknesses, such as economic inequality, exploitation of resources, and financial crises. Al-falah is a concept of welfare in Islam that includes material and spiritual welfare. This concept offers solutions to a number of weaknesses of capitalism. By prioritizing moral values ​​and justice, al-falah can realize equitable and sustainable welfare. And is able to deliver a fair Islamic economy in the socio-economic field, so that it becomes a solution to the failure of the Capitalist economy.